Bulk plasmon polariton in hyperbolic metamaterials excited by multilayer nanoparticles for surface-enhanced Raman scattering (SERS) sensing - Liu, Runcheng; Zha, Zhipeng; Shafi, Muhammad; Li, Can; Yang, Wen; Xu, Shicai; Liu, Mei; Jiang, Shouzhen (Nanophotonics (Berlin, Germany), 2021)
The capability to support large wave vector bulk plasmon polariton (BPP) waves enables the application of hyperbolic metamaterials (HMMs) in sensing. However, there is a challenge arising from the excitation of BPP, and the highly confined polarization waves are unable to meet the requirements of practical application. In this study, an HMM/bilayer silver nanoparticles (Ag NPs) platform is proposed that allows the excitation and utilization of BPP for use as a surface-enhanced Raman scattering (SERS) substrate. According to the research results, the bilayer Ag NPs provide stronger plasmonic property and act as a light-matter coupler, so as to generate a large wave vector of scattered light and excite the BPP within the HMM. Besides, Ag NPs provide the nano antenna structure, and decouple the BPP into localized surface plasmon (LSP) that can be used directly to excite the electric fields. In addition, HMM produces a modulating effect on the plasmon resonance peak, which makes it possible to overlap the spectrum of resonance peak with excitation wavelengths, thus leading to a strong absorption peak at the incident laser wavelength region. Experimentally, the platform was applied to achieve SERS detection for adenosine molecules with a concentration of 10 M. It is believed that this plasmonic platform has a potential of application in surface-enhanced spectroscopy.